A prospective case controlled study of the short‐term outcome following hemicolectomy for benign compared with malignant colonic polyps. (March 2014) - Brigic, A.; Cahill, R. A.; Bassett, P.; Clark, S. K.; Kennedy, R. H.
Abstract Aim The number of patients diagnosed with advanced colonic polyps has increased due to screening. The outcome of hemicolectomy for benign lesions is poorly documented. We present a case‐matched study comparing the results of hemicolectomy for benign and malignant polyps performed in two institutions. Methods Data for consecutive patients undergoing surgery for benign colonic polyps (BCPs) were prospectively collected in two hospitals. Each patient was matched for age, sex, ASA grade, site and type of resection (laparoscopic, open and converted) with two controls who underwent surgery for colon cancer (CC). The length of stay (LOS) and 30‐day outcome were analysed adjusting for potential confounders. Multilevel linear and logistic regression analyses were performed. Results Forty‐six patients having hemicolectomy for BCP were matched with 81 patients with CC. The median size of BCP was 4 cm [interquartile range (IQR) 2.5–5.4 cm]. Patients with a BCP had a marginally longer LOS [median 5.5 (IQR 4–8) days and 5 (IQR 3–7) days (P = 0.04)]. Twenty‐one (46%) of 46 patients with BCP had a postoperative complication compared with 25 (31%) of 81 CC patients (P = 0.12, OR = 2.11, 95% CI 0.82–5.41). Four (9%) of 46 patients with BCP underwent re‐operation and a further three (7%) were readmitted compared with one (1%) and two (2%) of 81 patients with CC (P = 0.07 and 0.28). There was no mortality in either group. Conclusion Complications following hemicolectomy for BCP or CC are not significantly different. The results of the study provide further impetus to develop local full thickness colonic excision for benign colonic lesions as an alternative to major surgery.